AB0674 YKL-40 is the biomarker for the presence of interstitial pneumonia and pulmonary arterial hypertension in systemic sclerosis. (15th June 2017) - Furukawa, T; Matsui, K; Kitano, M; Yokoyama, Y; Sekiguti, M; Azuma, N; Sano, H
Abstract : Background: SSc is a refractory of connective tissue disease that causes fibrosis of the skin and various organs. Recently, it is attention to 2013 ACR/EULAR classification criteria because can diagnose early phase before causing skin involvement in SSc. Thus, we considered that YKL-40 which is known to be involved in inflammation, tissue fibrosis and remodeling, is useful marker for evaluating early diagnosis and complications in SSc. YKL-40 is a chitinase-like protein and expressed in the synovial membrane and cartilage fibroblast cells in Rheumatoid Arthritis. Several cases of relationship between SSc and YKL-40 have been reported overseas, but it is unclear. Our report is the first in Japan. Objectives: We investigated serum YKL-40 levels and examined immunohistochemistry (IHC) with YKL-40 of cutaneous tissue in SSc patients. To clarify YKL-40 is useful biomarker in early diagnosis in the presence or absence of complications in Japanese SSc patients. Methods: Between August 2014 and March 2016, we treated 57 SSc patients in our department. We excluded infection, malignant disease, and other active complication may be a factor that increases YKL-40 levels. The patients were divided into 4 groups depending on whether suffered IP or PAH, which can affect the prognosis. Group1 (n=30) did not suffer from either IP or PAH, Group2 (n=12) suffered from IP, Group3 (n=7) suffered from PAH, and Group4 (n=8) suffered from both IP and PAH. YKL-40 levels in 4 groups and a control group of healthy individuals (n=13) were measured by ELISA. And age percentile strata of YKL-40 were calculated because serum YKL-40 levels have reported to rise with age; YKL-40 age percentile = 100/(1 + (Serum YKL-40 levels -3 ) × (1.062 age ) × 5000). IHC with YKL-40 of skin biopsy tissue from patients and controls was performed to investigate YKL-40 expression. Results: YKL-40 age percentile were elevated in Group1 compared to controls (42.0±24.5 vs 21.8±15.6), and were elevated due to complications (Group2, 3, 4: 61.8±21.4, 88.9±8.2, 94.4±8.7), with a tendency for PAH to cause greater elevation. There was no significant difference between Group3 and Group4, and a significant difference was found between the other groups (p<0.05). IHC with YKL-40 revealed staining of the vessels in the superficial dermis in SSc and normal skin remained unstained. The ROC curve for PAH showed an AUC=0.959, and the most valid cut-off levels of YKL-40 age percentile was 85.2 (sensitivity 86.7% and specificity 92.8%). Conclusions: Our report is the first report of IHC with YKL-40 in SSc. IHC suggest that YKL-40 may be further elevated by angiogenesis caused by microcirculatory damage in SSc. Our results suggest that YKL-40 may be very useful biomarker for diagnosing SSc and complications associated with microvascular lesions. References: Cross-sectional evaluation of YKL-40 serum concentrations in patients with systemic sclerosis. Relationship with clinical and serological aspects of disease. La Montagna G, D'Angelo S, Valentini G. J Rheumatol. 2003;30(10):2147–51. High serum levels of YKL-40 in patients with systemic sclerosis are associated with pulmonary involvement. Nordenbaek C, Johansen JS, Halberg P, et al. Scand J Rheumatol. 2005;34(4):293–7. Plasma YKL-40 levels in healthy subjects from the general population. Bojesen SE, Johansen JS, Nordestgaard BG. Clin Chim Acta 2011; 412(9–10): 709–12. Disclosure of Interest: None declared